مشكل حديث "إنما الشؤم في ثلاثة: الفَرَس، والمرْأَة، وَالدَّار" وتحليل الأبعاد التأويلية: Engagement with the Problematic Hadith, “Ill Omen Lies in Three: The Horse, the Woman, and the House”: An Analytical Examination of Its Interpretive Dimensions - Zakir Aras; Mohammed Abullais al-Khairabadi (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study examines Prophetic hadiths related to ill omen (ṭiyarah) and superstition, focusing on the variability of their narrations and interpretive approaches. The findings indicate that hadiths concerning ill omen in horses, women, and houses differ in degrees of authenticity and associated conditions, suggesting that their applicability is context-dependent rather than universal. When presented as commentary, these narrations highlight the need for careful scrutiny to reconcile differences and prevent apparent contradictions. The analysis demonstrates that ill omen and superstition do not reside inherently in the nature of things. Rather, Allah created all things for humanity’s benefit, establishing a baseline of permissibility and utility. Perceiving objects or events as inherently inauspicious reflects an unfounded negative presumption about Allah’s nature, which stands in opposition to Islamic teachings that encourage trust (tawakkul) in Him. Additionally, this study underscores the importance of critically evaluating hadith commentaries that attribute ill omen to external factors—such as an unfavourable neighbour—arguing that such interpretations may not align with the original text’s purpose and context. The emphasis on horses, women, and houses, frequently encountered in daily life, appears intended as a cautionary directive rather than an absolute statement of ill omen. ʿĀʾishah’s astonished reaction to Abu Hurayrah’s narration illustrates the need to consider variant transmissions and understandings of the hadith. Her perspective, supported by scholars like Ibn Qutaybah and Imam al-Ṭaḥāwī, merits significant consideration for a more accurate interpretation. Integrating these insights with contemporary scholarly approaches can lead to a deeper and more nuanced understanding of these hadiths.